Fulfillment of Wife and Children's Support: Comparison of Countries in Southeast Asia (Indonesia and Brunei Darussalam) - Nur Hastuti Bima Putri; Muhammad Maghfurrohman; Aaz Jidatul Haz, Zulkarnain; Zulkarnain; Lalu Muhammad Nurul Wathoni (al-Afkar, Journal For Islamic Studies, 2024)
One of the basic things for married couples is to sail the household together and have children. Apart from that, the rights and obligations that each partner must fulfill are important tasks for creating a harmonious household. One of the main rights and obligations for the continuity of life is providing support by the husband for his wife and children. Support is often a topic of discussion in Islamic family law, both in terms of providing maintenance while still in the status of husband and wife or after divorce. To avoid such things so that inequality does not occur in the relationship between husband, wife and children, the law has regulated it in such a way as to create, organize and protect each individual's right to support in accordance with his or her responsibilities. Meanwhile, the results of this research are in matters of nafaqah, the compilation of Islamic law (KHI) number 1 of 1974 does not explain it completely, but it regulates a lot about the rights and obligations of husband and wife. Meanwhile, the right to support wives and children in the Brunei Darussalam family is regulated in the 1999 Islamic Law Compilation Law, referred to in the sekyen which contains all aspects of women inside the household and outside the household and was revised in 2000, chapter 190 of the Law on Marriage for Women (married women).